Testing The Activity Of Antimicrobial Cream Formulation Of Ethanol Extract Of Kedondong Leaves (Spondias Dulcis) Against Bacteria Propionibacterium Acnes And Staphylococcus Aureus - Octora, Debi Dinha; Agnestine Jeliana Nababan; Pratiwi Christa Simarmata (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2024)
One of the causes of infection in acne is bacteria, such as Propionibacterium acnes and Staphylococcus aureus. Kedondong leaves have been used to treat diseases caused by bacteria. The purpose of this research is to: formulate a cream preparation containing ethanol extract of kedondong leaves and assess whether the cream preparation has antibacterial activity against P. acnes and S. aureus bacteria. The research method employed in this study is experimental, involving the following steps: preparation of ethanol extract of kedondong leaves using the maceration method with 96% ethanol solvent, formulation of the cream with a base consisting of cetyl alcohol, liquid paraffin, albumen vaseline, and distilled water. It is made in three concentrations of extract: F I with 10%, F II with 15%, and F III with 20%. Subsequently, the evaluation of the preparation was conducted, including physical stability evaluation, homogeneity, and antibacterial activity test against P. acnes and S. aureus bacteria using agar diffusion method with disc paper. The research results indicate that the cream has good physical stability and homogeneity for 30 days of storage at room temperature. The antibacterial cream preparation containing ethanol extract of kedondong leaves showed antibacterial activity against P. acnes and S. aureus bacteria. The average inhibition zones against P. acnes for formulations I, II, and III were 12.25 mm, 16.15 mm, and 24.15 mm respectively, while for S. aureus, the average inhibition zones were 10.75 mm, 15.45 mm, and 17.55 mm respectively, and the Positive Control (Clindamycin Antibiotic) had an inhibition zone of 30.35 mm. Based on the obtained results, it can be concluded that the cream preparation containing ethanol extract of kedondong leaves has inhibitory activity against P. acnes and S. aureus bacteria.